The Inflammatory Cytokine Profile Associated With Liver Damage Is Broader and Stronger in Patients With Chronic Hepatitis B Compared to Patients With Acute Hepatitis B. (21st July 2021) - Johnson Valiente, Alexandra; Liem, Kin Seng; Schwarz, Kathleen B; Rosenthal, Philip; Murray, Karen F; Mogul, Douglas; Teckman, Jeffery; Rodriguez-Baez, Norberto; Schwarzenberg, Sarah Jane; Feld, Jordan J; Wong, David K; Lewis-Ximenez, Lia L; et al.
Abstract: Liver damage in hepatitis B is immune driven and correlates with inflammatory markers in patient serum. There is no comparison of these markers to determine if inflammatory profiles are distinct to different types of liver damage across patients at different stages of disease. We measured 25 inflammatory markers in patients with acute hepatitis B and chronic hepatitis B with hepatitis B e antigen seroconversion and chronic patients stopping nucleoside analogue therapy. Myeloid markers dominated the inflammatory profile in all stages of hepatitis B. More inflammatory markers were detectable in chronic patients, including elevated concentrations of cytotoxic effectors Fas ligand, TRAIL, and TNF-α. Abstract : The myeloid marker CD163 dominated the inflammatory profile across liver damage associated with different stages of hepatitis B virus infection. While profiles overlapped substantially, chemokines and cytotoxic effector molecules were elevated in chronic hepatitis B patients with liver damage.